The good son [large type] : JFK Jr. and the mother he loved - Andersen, Christopher P. (Thorndike Press, a part of Gale, Cengage Learning, 2014)
At the heart of The Good Son is the most important relationship in JFK Jr.'s life: that with his mother, Jackie Kennedy Onassis. Andersen explores JFK Jr.'s reactions to his mother's post-Dallas depression; how Jackie felt about the women in her son's life; and the senseless plane crash that took his life. This riveting, bittersweet biography offers new insights into the intense, tender, often stormy relationship between this iconic mother and son.